2012
DOI: 10.1038/icb.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

TNFRp55 controls regulatory T cell responses in Yersinia‐induced reactive arthritis

Abstract: In addition to its well-known pro-inflammatory effects, tumor necrosis factor (TNF) displays anti-inflammatory activities through mechanisms poorly understood. Previously, we reported the development of severe chronic Yersinia enterocolitica-induced reactive arthritis (ReA) in mice lacking the TNF receptor (TNFR)p55. As regulatory T (T(reg)) cells limit chronic inflammation, here we aim to investigate the expansion and function of CD4(+)CD25(+)FoxP3(+) T(reg) cells in the ReA animal model. The number of T(reg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Recently, we reported that TNFRp55 modulates macrophage functions in response to Yersinia LPS stimulation suggesting an essential regulatory role of TNF via TNFRp55 signaling [93]. Furthermore, we have reported that this pathway controlled the induction and function of Treg cells through differential regulation of cytokine production [69]. Our data support the concept that TNFRp55 signaling may participate in the modulation of immune response in ReA, suggesting caution in the use of TNF blockers in cases of chronic ReA.…”
Section: Treatmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Recently, we reported that TNFRp55 modulates macrophage functions in response to Yersinia LPS stimulation suggesting an essential regulatory role of TNF via TNFRp55 signaling [93]. Furthermore, we have reported that this pathway controlled the induction and function of Treg cells through differential regulation of cytokine production [69]. Our data support the concept that TNFRp55 signaling may participate in the modulation of immune response in ReA, suggesting caution in the use of TNF blockers in cases of chronic ReA.…”
Section: Treatmentsupporting
confidence: 81%
“…In line with these results, we detected higher IL-17 and IFN-γ levels in regional lymph nodes of TNFRp55 −/− mice with Y. enterocolitica-induced ReA and significantly increased number of CD4 + IL-17 + cells in these mice compared to their counterpart wild-type [68]. In addition, in this animal model we observed decreased amounts of IL-10 and Treg cells at arthritis onset (day 14 after infection) in contrast with chronic stage of arthritis [69]. These works and others advocate the idea that in ReA, a specific cellular immune response take place in the joint and chronic stimuli allows to the cells maintain the inflammatory process for long periods [70].…”
Section: (1) Pathogenic Bacteria Attach and Invade The Intestinal Episupporting
confidence: 47%
“…Previous studies have indicated that neutralization of TNF during rheumatoid arthritis treatment elicited a significant population of Tregs. And the ablation of p55TNF in reactive arthritis mice resulted in a reduced Tregs number and activity indicate that TNF signaling through p55TNFR and p75TNFR is important to the regulation of Treg cell function6869. Another possible mechanism associated with defective T cell responses might be that sustained p55TNFR signaling induces T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Yersinia enterocolitica was confirmed as a pathogen of Yersinia and it has been shown that it can also produce Yersinia pseudotuberculosis-derived mitogen, a super antigen that is associated with ReA [33]. A later article [34] revealed the involvement of p40, a common subunit of heterodimeric IL-12 and IL-23, in increasing both IFN-γ and IL-17 production under TNFR p55 deficiency. Taken together, these data indicate that, in the absence of TNFR p55 signaling, Th1 and Th17 effector cells may have a critical function that sustains the inflammatory response in ReA processes.…”
Section: Pathogenesis Of Reamentioning
confidence: 99%
“…IV, Lactobacillus casei can inhibit the expression of TNF-α, IL-17, IL-23, IL-1 and IL-6 in intestinal lymph nodes which lead to protective role in ReA. V, TNFRp55 regulates the cytokine production and enhanced the production of IFN-γ and IL-17, which developed severe chronic Yersinia enterocolitica-induced (ReA) [32][33][34]. (Chlamydia trachomatis) infection is the most common factor causing ReA, which can persist in the host and cause typical reactive arthritis [2].…”
Section: Pathogenesis Of Reamentioning
confidence: 99%